Identifikasi Manajemen Pelayanan Publik Dengan Pendekatan Smart Governance Pada PPSDM Migas - Nur Lailia Widianingsih; Himmatul Izza Nur Fadhila; Herwening Siwi Ekayanti; Muhammad Farhan Wildan; Lika Indriyani (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2023)
Public service is the implementation of the obligations of the government apparatus as a state servant, a public service intended to fulfill the rights of citizens and create good governance. This research aims to find out the management of public servants with a good governance approach at the Center for Human Resources Development of Oil and Gas. The benefits of this research as a material for the study and evaluation of public services in the Center for Human Resources Development of Oil and Gas in order to realize the principles in value good governance. The results of this study show that the quality of public service management at PPSDM Migas has been done well. This can be seen from the percentage of achievements on the five policy pillars used to realize optimization of service performance. In addition, public services in PPSDM Migas have also been in accordance with good governance by involving internal and external parties in conducting public sector management in accordance with the needs of the community, especially in the field of oil and gas.